A Capital Adequacy Buffer Model - David Allen; Michael McAleer (Tinbergen Institute, 2013)
In this paper, we develop a new capital adequacy buffer model (CABM) which is sensitive to dynamic economic circumstances. The model, which measures additional bank capital required to compensate for fluctuating credit risk, is a novel combination of the Merton structural model which measures distance to default and the timeless capital asset pricing model (CAPM) which measures additional returns to compensate for additional share price risk.
Keywords: G01; G21; G28; 330; Credit risk; Capital buffer; Distance to default; Conditional value at risk; Capital adequacy buffer model